PENGARUH REKRUITMEN, PENGEMBANGAN KARIR, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAKERTRANSDUK PROVINSI JATENG - Heru Sri Wulan; Leonardo Budi Hasiholan (ITB AAS INDONESIA Surakarta, 2021)
Policies to improve employee performance need to be analyzed further. In this study will analyze the effect of recruitment, career development, work discipline and work motivation on employee performance at Dinakertrasduk, Central Java province. In this study, samples were taken as many as 100 people using purposive sampling technique, namely sampling based on criteria, among others: employees who are taken as samples are employees who have worked for at least 3 years. The data analysis method used in this research is validity, reliability, multiple linear regression, t test. The results show that with multiple linear regression analysis, it can be shown by the regression equation Y = -0.16X1 + 0.862X2 + e1. From the results of the analysis above, it can be concluded that the variables of recruitment and career development do not increase, which affects work motivation. while the regression equation analysis Y2 = 0.506X3 + 0.271Y1 + e2 from the results of the analysis above, it can be concluded that discipline and motivation variables increase, affect performance. The hypothesis that has been carried out in this study can be concluded that: a. There is a positive and significant effect of recruitment on motivation. b. There is a positive and significant effect of career development on motivation. c. There is a positive and significant effect of work discipline on performance. d. There is a positive and significant influence of motivation on performance in Dinakertrasduk Povinsi Central Java. Suggestions that can be put forward in this study include: company leaders to pay attention to things that can increase employee motivation and performance, among others: to further promote career development of employees of Dinakertrasduk, Central Java Province. and improve work discipline of the employees of the Central Java Province Dinakertrasduk. and pay attention to the work motivation of its employees.